1965
DOI: 10.2466/pr0.1965.17.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Further Test of the Deprivation Trace Hypothesis

Abstract: 32 rats were used to test the deprivation-trace hypothesis of O'Kelly and Heyer (1951). In a 2 × 2 × 2 factorial design the following variables were manipulated: delay between saline injection and bar-press testing, 30 min. vs 240 min., presence or absence of food during the delay period, and schedule of reinforcement, VI-¼ min. vs VI-1 min. The only significant differences were the main effects of schedule and delay. The prediction was supported, but alternative interpretations not requiring the hypothesis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1967
1967
1973
1973

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The motivational properties of NaCI injections have been studied by Beck and Carter (1965), Wayner et al (1970), Winer (1971), and others. Leverpress response rates on both CRF (continuous) and short FR (fixed-ratio) schedules increase with increasing concentrations of NaCl and then decrease at high concentrations (Stricker, 1968; Wayner et al, 1970).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The motivational properties of NaCI injections have been studied by Beck and Carter (1965), Wayner et al (1970), Winer (1971), and others. Leverpress response rates on both CRF (continuous) and short FR (fixed-ratio) schedules increase with increasing concentrations of NaCl and then decrease at high concentrations (Stricker, 1968; Wayner et al, 1970).…”
mentioning
confidence: 99%
“…However, the influence of NaCI-induced thirst on behavior under nonregulatory-type schedules (e.g., variable interval or VI) is unclear. Beck and Carter (1965) showed that NaCI injections could apparently induce leverpressing for VI water reinforcement in sated rats previously trained to press for water. Increased response rates following longer delays after NaCl injections suggested that the NaCl was, in fact, motivating the previously learned behavior.…”
mentioning
confidence: 99%